Methodological Aspects of Conceptual Design of an Agricultural Machine by The Case of a Tunnel Spraying Machine (Agricultural Engineering, 2017)
The article presents the procedure of determination of a structural form of an agricultural machine which encompasses methodological aspects of design related to the division of the basic objective function into member functions, multi-variant solutions and synthesis of astructural form (a virtual prototype of an agricultural machine). The suggested course of proceeding was presented by the case of a design of a tunnel spraying machine. This example reflects well and includes the specificity of the design object in the form of an agricultural machine with specific technical and agro-technical requirements. Attention was paid to the aspects related to methodology of selection of fractional solutions based on previously defined criteria.